Socio-economic Empowerment of Farmwomen in Madhya Pradesh Through Suitable Technological Interventions: A Krishi Vigyan Kendra (KVK) Approach (Indian Journal of Extension Education, 2012)
Women are the backbone of an agricultural workforce and do the most tedious and back-breaking tasks in agriculture, animal husbandry and homes but her hard work has mostly been unpaid and unrecognized worldwide. With this backdrop, there is a need for social and economic empowerment of women. Indian Council of Agricultural Research (ICAR) established a vast network of 575 KVKs with provision of one home scientist in each KVK for conducting the mandated activities like On Farm Trials (OFTs), Front Line Demonstrations (FLDs) and Training, with special focus on farm women to increase their knowledge, enhance their skill and change their attitude and for the overall improvement of farm women. Zonal Project Directorate, Zone VII comprising 93 KVKs spread over Madhya Pradesh, Chhattisgarh and Odisha. In Madhya Pradesh (M.P.) there are 47 KVKs with 28 Home Scientists working in the field of women in agriculture for the upliftment of status of farm women. A technological module was developed and popularized for proper working of home scientists and to overcome the problems of farm women which contain status of farm women, problems of farm women, institutional arrangements, case studies, outcomes of the activities, problem inventory and process for the development of modules in terms of technology assessment, refinement and demonstration of technology/ product/ methodology and capacity building of farm women. On this basis, we identified 48 problems of farm women related to low income, drudgery reduction, nutritional security and value addition. Further, to solve above problems we conducted 32 OFTs, 30 FLDs and 278 trainings in Madhya Pradesh. All these interventions resulted in adoption of 45%, 68%, and 85%,which resulted in increases of 20-25% additional income. Therefore, if the module used properly, it will surely help in improving the livelihood and quality of life (QOL) of the farm women in the region.